The Importance of Early Intervention for Children with Autism Spectrum Disorder - Nurfallah, Restu; Azmi, Sarah Nurul; Dhiaulhaq, Nadia Salsabila; Astuti, Eka Yuli (Angstrom Centre of Education, 2024)
Autism spectrum disorder is a comprehensive developmental disorder that can result in barriers in several aspects of development such as social, communication, and behavioral aspects from mild to severe. The symptoms of autism generally appear before the child reaches the age of 3 years. Currently, the exact cause of autism has not been found yet, but some studies suggest that the cause of autism is a disturbance in the function of the central nervous system caused by abnormalities in brain structure. Disorders experienced by children with autism are disorders in the field of social interaction such as the absence of eye contact with the interlocutor, in the field of communication both verbal and non-verbal. Intensive and optimal early intervention that can be useful for the treatment of autistic children is commonly referred to as therapy.